Ice Forces on Model Bridge Piers - Haynes,F D; Sodhi,D S; Kato,K; Hirayama,K (1983)
Small-scale laboratory experiments were conducted on model bridge piers in the CRREL test basin. The experiments were performed by pushing model ice sheets against structures and monitoring the ice forces during the ice/structure interaction. The parameters, varied during the test program, were the geometry of the bridge piers and the velocity, thickness, and flexural strength of the ice. The results are presented in the form of ice forces on sloping and vertical structures with different geometries. During ice action on sloping structures, a phenomenon of transition of failure mode from bending to crushing was observed as the ice velocity was steadily increased. (Author)